Behaviour after cerebral lesions in children and adults. 1962. - Teuber, H; Rudel, R (2008)
It is generally believed that brain injuries vary in their effects according to the age at which they are sustained, but the nature and extent of these differences remain elusive. A full enquiry requires, ideally, the study of strictly comparable lesions in the young and the old, the opportunity for follow-up examinations extending over decades in both groups and, lastly, the availability of behavioural tasks for which normal attainment is known, and which are equally applicable to the brain-injured child and the brain-injured adult. The investigations of behavioural changes after brain injury in children and adults, reported here, are far from fulfilling all these requirements. In particular, these studies are obviously deficient with regard to our first postulate, that of comparable lesions. Identical lesions in children and adults are so rare that one is often forced to turn to animal experiments as a supplementary source of information. Admittedly, animal experiments introduce phylogenetic differences in addition to the ontogenetic ones; yet available animal studies can help to indicate some of the directions in which the answers to the ontogenetic question may be sought. Accordingly, we begin this account with a brief consideration of animal experiments, before presenting some of the results obtained in our laboratory in students of brain-injured about and children. © 2008 Blackwell Publishing Ltd.